دراسة صومعة محلية تحت تأثير الأحمال الزلزالية باستخدام التحليل بالسجلات الزمنية الصنعية - تريكية علي (Latakia University Journal -Engineering Sciences Series, 2019)
دراسة صومعة محلية تحت تأثير الأحمال الزلزالية باستخدام التحليل بالسجلات الزمنية الصنعية علي تريكية الصوامع هي منشآت هندسية خاصة لتخزين المواد الحبيبية، ونتيجة ازدياد احتياجات السكان أدت إلى زيادة بناء هذه المنشآت، تتعرض الصوامع إلى العديد من أنواع التحميل بسبب ملء وتفريغ المواد المخزنة، والظروف الحرارية، انفجار الغبار، انهيار الهيكل الداخلي، أحمال الرياح خاصة للصوامع الفارغة، الزلازل، تختلف معظمها عن أنواع التحميل للمنشآت الأخرى، وتختلف استجابات الصوامع لأنواع التحميل الشائعة أيضًا عن تلك الخاصة بالعديد من المنشآت الأخرى بسبب الحجم الكبير للصوامع، يعتبر تصميم الصوامع معقدًا ونتيجة لارتفاع معدل الفشل في الصوامع، وخاصة بالنسبة للأحمال الزلزالية بين الحالات المذكورة أعلاه، لا تزال الصوامع تحتفظ بأهميتها كموضوع بحثي، إلا أن القليل من الدراسات المتعلقة باستجابة هذه المنشآت للحمولات الزلزالية يمكن العثور عليها، والقليل من الكودات الوطنية أو الدولية تشمل الاشتراطات المتعلقة بالتصميم الزلزالي للصوامع. الصومعة المختارة للدراسة قائمة في معمل اسمنت طرطوس نفذت سنة 1982 ويخزن فيها (المواد الأولية لصناعة الإسمنت –الإسمنت –المواد المضافة للإسمنت ), والصومعة مدروسة وفق الكود الألماني وهي غير مدروسة على الزلازل. يهدف هذا البحث إلى دراسة الصومعة المنفذة من خلال حالة دراسة باستخدام التحليل بالسجلات الزمنية الصنعية، وذلك بإجراء دراسة تحليلية تطبيقية على نموذج فراغي (3D) للصومعة حيث استخدمت سجلات زمنية لزلازل حقيقية تم تقييسها باستخدام طريقتي مجال الزمن ومجال التردد لتلائم طيف الاستجابة للكود العربي السوري. Silos are special engineering installations for the storage of granular materials. As a result of the increasing needs of the population, the construction of these facilities has increased. Silos are exposed to many kinds of loading due to filling and unloading of stored materials, thermal conditions, dust explosion, internal structure breakdown, wind loads especially for empty silos, earthquakes , Most of which differ from the load types of other facilities. The silo responses to loading types are also different from those of many other facilities due to the large silo size. Silos design is complex. As a result of the high rate of failure in silos, especially for seismic loads among the above cases, silos remain important as a research topic. However, few studies on the response of these installations to seismic loads can be found, and few national or international codes include requirements for seismic design Silos The selected silo for the study is located in the Tartous Cement Factory. It was implemented in 1982 and stores it (raw materials for the cement industry - cement - additives for cement). Silos are studied according to the German code and are not studied on earthquakes The purpose of this study is to study the silo carried out through the case of a study using the synthetic time histories analysis by conducting an applied analytical study on a 3D model of the plume, were used for real earthquakes that were scaling by using the time domain and the frequency domain to suit the Syrian response spectrum.